Cleft Lip With or Without Cleft Palate: Prenatal Diagnosis, Chromosomal Abnormalities, Associated Anomalies and Postnatal Outcome in 18 Fetuses - Cem Batukan; Mahmut Özgün; Mustafa Başbuğ; Hülya Akgün (Medical Network, 2007)
OBJECTIVE: The aim of this study was to present our experience with prenatal diagnosis of cleft lip and/or palate (CL/P) and to determine the relationship between facial clefts, associated malformations and chromosomal anomalies. STUDY DESIGN: Data of 18 fetuses with prenatally diagnosed CL/P were retrospectively analyzed. Postnatal outcome and incidence of additional malformations and chromosomal abnormalities were determined. RESULTS: Postnatal findings confirmed that the type of cleft was median CL+P (n=3), bilateral CL+P (n=5), unilateral CL+P (n=5), unilateral CL (n=5). Eight cases were diagnosed at or before 24 weeks of gestation. Eleven fetuses (%61) had additional structural anomalies. Abnormal fetal karyotype was present in 5 fetuses (two cases with trisomy 13 and three cases with trisomy 18). All fetuses with isolated CL/P survived after surgery. Termination of pregnancy was requested in nine fetuses with additional anomalies and/or chromosomal anomalies, whereas one each of the fetuses died in utero or early neonatal period. CONCLUSION: In pregnancies complicated with CL/P, patients should be informed about the risk of associated anomalies, chromosomal abnormalities and syndromic conditions.